Layout analysis and restructuring in the pre-assembly sector of the serial line in a furniture industry - Trevisol, Janyel (Seven Editora, 2023)
The constant search to reduce operating costs, as well as to increase productivity and reduce internal problems, has been the target of companies to remain inserted within a highly competitive market. To this end, internal changes are part of the strategies to achieve these goals. The present work aims to implement a new layout with optimization of the productive space in the pre-assembly sector of the serial line, in a furniture industry. The method used for the elaboration of this work was action research, which enabled a detailed analysis and allowed the implementation of a new physical arrangement, compatible with the company's manufacturing process. As a result of the work, it was obtained clarity of the process, optimization of the physical space, reduction of material movements and transports, reduction of inventory in process, ease in internal logistics flows due to the well-dimensioned corridors, better visibility of the sector, organization and cleaning, more efficient production control and reduction of waste. DOI:https://doi.org/10.56238/interdiinovationscrese-036